MAIN SOURCES OF SUGAR INTAKE OF ADOLESCENTS IN DAERAH ISTIMEWA YOGYAKARTA PROVINCE, INDONESIA - Yohannes Willihelm Saleky; Nipa Rojroongwasinkul (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: There was 16.9% of population in Daerah Istimewa Yogyakarta (DIY) Province with excess sugar intake, higher than national prevalence 4.8%. Nevertheless, there has not been studied yet about sugar intake of adolescents in this province. The adverse effects of excessive sugar intake leads to cardiovascular diseases (CVDs) and type 2 diabetes mellitus, directly and indirectly through body weight and fat gain in later life. Twenty to forty percent of overweight adolescents are twice likely todevelop CVD and seven times greater risk of atherosclerosis. Thus, it is important to prevent NCDs since the behaviours established during adolescent have life-long consequences particularly regarding NCDs in DIY Province. This study aims to assess the daily sugar intake and the main sources of sugar of adolescents in DIY province, Indonesia. Methods: This is an observational study with cross sectional design with the targeted population of all the adolescents aged 15 to 17 years old in urban and rural area of Daerah Istimewa Yogyakarta province, Indonesia. Four schools were chosen with the total sample of 380 students. Four instruments were used in this study i.e. general information questionnaire, semi-quantitative food frequency questionnaire (SFFQ), digital weighing scale and BIA analysis, and microtoise. Mann Whitney test was used to analyze the difference of daily sugar intake between urban and rural area. Statistical tests were considered as significant at P <0·05. Results: Means of daily sugar intake of adolescents were 107.0 g and 87.4 g in urban and rural area respectively. In urban area, the minimum intake of sugar was 15.2 g/day and the maximum intake of sugar was 317.2 g/day. Whereas in rural area, the minimum intake of sugar was 17.2 g/day and the maximum sugar intake was 87.4 g/day. There was a significant difference between average daily sugar intake of adolescents in urban and rural area (P= 0.004). Conclusion: The main sources of sugar intake of adolescents both in urban and rural area were sweetened beverages, additional foods and sweet snacks respectively.